Revisiting the green geographies of welfare planning: an introduction. Issue 3 (3rd July 2022) - Pries, Johan; Qviström, Mattias
ABSTRACT: The history and legacy of green planning of the welfare era have largely been overlooked within research, or critiqued due to its limited urban qualities and poor design. This omission has left its role in the development of the Welfare society largely unexplored. Therefore, this special issue revisits the green geographies of welfare planning, to reveal its importance as a matter of welfare and as a set of geographies that goes beyond the contemporary norm of the compact city. The revisits take two forms: historical studies to elucidate the original ideas and geographies of the planning, and revisits to sites currently challenged by new urban or planning ideals. This introduction presents the papers, reflects on previous research, and concludes with a few comments on the need for further studies on green planning and the landscape legacy of the welfare era.